Pengaruh Ketinggian Tempat Kandang Terhadap Kualitas Fisik Telur Ayam Ras di Kabupaten Tabanan, Bali: The Effect of Cage Height on the Physical Quality of Broiler Chicken Eggs in Tabanan Regency, Bali - Rejeki, I Gusti Ayu Dewi Seri; Mardewi, Ni Ketut; Janurianti, Ni Made Defy (Fakultas Peternakan Universitas Jambi, 2026)
Background: Laying hens can produce eggs in approximately six months, with a production rate of around 250-300 eggs per hen per year. Egg production is heavily influenced by genetic and environmental factors. High temperatures in the hen's rearing environment can negatively impact the health and productivity of the hens. Purpose: This study aims to determine whether the height of the cage affects the physical quality of chicken eggs in Tabanan Regency, Bali. Method: This study uses analysis of variance (ANOVA) for normally distributed data, and if significant (p <0.05), it continues with Duncan. Results: Chicken eggs produced in highlands have a yolk color ranging from 8-9, while those in medium altitudes show a color value of 6-7. The pH value of chicken eggs does not differ significantly at each cage altitude, ranging from 7.0-8.0. The height of the laying hen cage does not affect the yolk index (IKT) and egg white index (IPT). Chicken eggs obtained in highlands have a lower haught unit value compared to those in medium altitudes, meaning the overall quality of chicken eggs in medium altitudes is better, indicating better chicken metabolism when raised in medium altitudes. This is supported by the number of laying hen cages that are more common in medium altitude areas, indicating that laying hen farmers produce better chicken eggs in medium altitudes. Conclusion: The height of the laying hen cage has a significant effect on the color and haught of the chicken egg unit, but does not have a significant effect on pH, egg yolk index and egg white index.